Cancellation of a preventive measure in the form of detention under martial law in the context of Art. 616 of the CPC of Ukraine - A. H. Harkusha (Law and Safety)
The actual changes to the CPC of Ukraine made in connection with the introduction of the martial law have been highlighted. Peculiarities of cancellation and change of preventive measures in the form of detention under martial law in the context of Art. 616 of the CPC of Ukraine have been studied. With the introduction of martial law in Ukraine on February 24, 2022, in connection with the military aggression of the Russian Federation, a number of significant changes have been made both to section IX-1 and to other sections of the Criminal Procedure Code of Ukraine. The essence of the procedure for canceling and changing a preventive measure in the form of detention under martial law has been revealed, namely, it has been clarified that this process is complex and contradictory, as there is no clear mechanism for its practical application.